50 th birthday of Christian von Ferber (Condensed Matter Physics, 2011)
On May 15, 2011 Christian von Ferber –
member of the Editorial Board of “Condensed
Matter Physics” and renowned expert in the
fields of soft matter physics and complex systems
– celebrated his 50th birthday.